2021
DOI: 10.1172/jci.insight.149819
|View full text |Cite
|
Sign up to set email alerts
|

CD7-deleted hematopoietic stem cells can restore immunity after CAR T cell therapy

Abstract: Conflict of interest:MYK is an inventor on patent US62/250,561 relating to methods for gene editing in hematopoietic stem cells to enhance the therapeutic efficacy of antigen-specific immunotherapy. MLC has employment/ownership/ equity and is a founder of Wugen, receives consultant fees from RiverVest, and receives royalties from NeoImmuneTech Inc. TAF is a consultant and has equity/royalties from Wugen; has research support from ImmunityBio, Affimed, Compass Therapeutics, and HCW Biologics; and is an advisor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 32 publications
(32 reference statements)
2
17
0
Order By: Relevance
“…knocked out CD7 in hematopoietic stem cells (HSCs) and found that these CD7-KO HSCs differentiated into CD7-negative T-cells and NK cells that exhibited effector functions after transplantation into mice. This study suggests that such an approach could resolve T-cell immunodeficiency caused by CD7-CAR therapy, altogether providing a potential new approach for the development of CD7 CAR ( 85 ). In 2022, Dai et al.…”
Section: Car-t Therapy For Non-b-cell Acute Leukemiamentioning
confidence: 87%
“…knocked out CD7 in hematopoietic stem cells (HSCs) and found that these CD7-KO HSCs differentiated into CD7-negative T-cells and NK cells that exhibited effector functions after transplantation into mice. This study suggests that such an approach could resolve T-cell immunodeficiency caused by CD7-CAR therapy, altogether providing a potential new approach for the development of CD7 CAR ( 85 ). In 2022, Dai et al.…”
Section: Car-t Therapy For Non-b-cell Acute Leukemiamentioning
confidence: 87%
“…These CD7-KO HSCs generated functional CD7 - T cells and NK cells, although they are different from CD7 + T cells/NK cells. As the results, the mice are protected from CD7-CAR-T cell-induced immunodeficiency ( 170 ). Similarly, infusion of CD33-KO HSCs is able to restore immunity upon CD33-CAR-T cell treatment against AML ( 171 , 172 ).…”
Section: Mitigating Toxic Adverse Effects Associated With Car-t Cell ...mentioning
confidence: 87%
“…Screening for novel and specific antigens restricted to malignant cells, equipping CAR-T cells with safety switches, and post-CAR SCT may be beneficial in controlling immunodeficiency [63][64][65][66]. In addition, transplanting stem cells with deletion of target antigen genes before CAR-T cell infusion may be a promising strategy to prevent immunodeficiency [67]. All these strategies will require in-depth evaluations to validate their safety and efficacy in preclinical and clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…CD7-negative cells can tolerated well to CD7 UCAR-T cells [67]. Transplantation of gene-edited stem cells may be applied to other targets, such as CD5.…”
Section: Review Hematology and Oncology Discoverymentioning
confidence: 98%